Clinical utility of breast pathology data: implications for practising pathologists. Issue 8 (19th July 2022) - Deb, Rahul; Tan, Puay Hoon
Abstract : In breast cancer, the quality of the pathology services is of paramount importance as inevitably, the pathologist makes the confirmatory diagnosis and provides prognostic and predictive information, informing treatment plans directly. Various national and international organisations provide a pathology reporting minimum dataset (MDS) to ensure consistency in reporting. While the use of MDS promotes clarity, there may be specific areas requiring the pathologist's input for individual patients and hence pathologists need to be aware of the clinical utility of pathology data to help tailor individualised patient treatment. In this article, we provide numerous examples of the role of pathology data in determining next steps in the patient pathway that are applicable to both the diagnostic and treatment pathways, including neoadjuvant treatment pathways. We also briefly discuss the important role and thereby the clinical utility of pathology data during the COVID-19 pandemic providing a template for the similar scenarios in the future if required.